A Case of Helicobacter cinaedi Bacteremia in an Asplenic Patient - Kim, Soo-Kyung (The Korean Society for Laboratory Medicine, 2012)
Helicobacter cinaedi is an enterohepatic species. It can cause bacteremia, gastroenteritis, and cellulitis, particularly in immunocompromised individuals, such as those with acquired immunodeficiency syndrome, malignancy, or alcoholism. There are no previous reports of H. cinaedi infection in Korea. A 71-yr-old man was admitted to the emergency room because of dyspnea on November 9, 2011. He had undergone splenectomy 3 yr ago because of immune hemolytic anemia. Chest plain radiography revealed bilateral pleural effusion. He developed fever on hospital day (HD) 21. Three sets of blood cultures were taken, and gram-negative spiral bacilli were detected in all aerobic vials. The isolate grew in tiny colonies on chocolate agar after 3-day incubation under microaerophilic conditions. This organism tested positive for catalase and oxidase, and negative for urease. The 16S rRNA gene sequence of this isolate exhibited 99.8% homology with the published sequence of H. cinaedi CCUG 18818(T) (GenBank accession no. ABQT01000054) and 98.5% homology with the sequence of Helicobacter bilis Hb1(T) (GenBank accession no. U18766). The patient was empirically treated with piperacillin/tazobactam and levofloxacin, and discharged with improvement on HD 31. To our knowledge, this is the first report of H. cinaedi bacteremia in an asplenic patient. Asplenia appears to be a risk factor for H. cinaedi bacteremia.